Commercial Video Games in School Teaching: Two Mixed Methods Case Studies on Students’ Reflection Processes - Rüth, Marco; Kaspar, Kai (Frontiers in Psychology, 2021)
Commercial video games are popular entertainment media and part of students’ media reality. While commercial video games’ main purpose is not learning, they nonetheless could and should serve as objects of reflection in formal educational settings. Teachers could guide student learning and reflection as well as motivate students with commercial video games, but more evidence from formal educational settings is required. We conducted two mixed methods case studies to investigate students’ reflection processes using commercial video games in regular formal high school teaching. In a double lesson, 29 students of a tenth-grade biology course (Study 1) and 17 students of a twelfth-grade advanced course on history (Study 2) played and discussed a commercial video game related to the current curricular topic. We examined the reflection processes of students in terms of their reactions to the teachers’ game-related statements and questions. Regarding teachers’ statements, students discussed several topics related to game enjoyment and the games’ representation of topic-related content. Regarding teachers’ questions, students discussed multiple goals in each game, how the games represented topic-related content, and how the games could be appropriate for learning. In Study 2, students additionally discussed emotions, stereotypes, violence, and the narrative related to the digital history game. We found that the discussions provided students opportunities to reflect on their game experiences and the current curricular topic as well as to practice media criticism. We further provide quantitative results on students’ perceived topic knowledge, on several facets of their learning motivation, and on their acceptance of video games. Overall, our findings illustrate the educational value of using commercial video games as objects of reflection.